Rheological blood properties in psoriatic arthritis: relationship with inflammation and cardiovascular risk - T V Korotaeva; E Y Loginova; D S Novikova; K V Esakova; N V Klimova; A A Novikov; E N Alexandrova; E L Nasonov; N N Firsov (Научно-практическая ревматология)
Objective. To study possibility of using blood rheological parameters as markers of inflammation and cardiovascular risk (CVR) in pts with psoriatic arthritis (PA). Material and methods. 130 pts (51 male and 79 female) with PA aged from 39 to 48 years (mean age 43 years) without clinical signs of coronary heart disease (CHD) and stroke were included. Duration of PA varied from 2 months to 42 years (mean 7 years), duration of psoriasis (PS) – from 5,5 to 26 years (mean 15 years). Main measures of erythrocyte aggregation (EA) including Kt (c-1) – total speed of erythrocytes aggregates formation, T (c) – time of linear erythrocytes aggregates formation, I2,5 [%] – parameter characterizing durability of most large erythrocytes aggregates, β (c-1) – hydrodynamic durability of erythrocytes aggregates were evaluated in erythroaggregometer by registration of intensity of inverse light scattering from blood sample. PA activity was measured with DAS4. CHD development risk score was determined considering traditional CVR factors – age, total cholesterol (TCH) and high density lipoproteins (HDLP) level, systolic blood pressure (SBP), presence of diabetes, smoking. Serum C-reactive protein (CRP) and fibrinogen concentration was measured with standard methods. Correlation analysis was performed with Spearman range correlation coefficient (R), Mann-Whitney (U) test was used for groups comparison and p<0,05 was considered as statistically significant level. Results. EA disturbances corresponding to 2nd stage of severity were present in all pts with PA. Significant correlation between EA parameters (T , Kt, I2,5, β) and DAS4 (R=-0,32/0,32/0,33/0,25, p<0,001) as well as significant correlation of all EA parameters (T , Kt, I2,5, β) with laboratory inflammation markers: CRP (R=-0,37/0,41/0,46/0,32), ESR (R=-0,34/0,35/0,42/0,26) and most strong – with fibrinogen (R=-0,55/0,55/0,49/0,32) were revealed. Significant correlations of all EA parameters and fibrinogen with CVR level was found in all pts (R=-0,31/0,35/0,23/0,22, p<0,001). In women relationship between EA parameters, fibrinogen and CVR level was stronger (R=-0,42/0,41/0,40/0,27). In men correlation between EA parameters, fibrinogen and CVR was not found. Conclusion. EA parameters in PA are biomarkers of inflammation and CVR.